Etyka w bankowości – dylematy pracownika bankowego - Lipiński, Czesław (Annales. Etyka w Życiu Gospodarczym, 2008)
Credibility and reliability of counter-partners are the most important features required forthe efficient functioning of financial markets. Violating these requirements is an important aspect ofthe operational risk, posed by the human factor – both internal (managers, employees) and external(customers, shareholders, competitors, supervisors). Therefore, having a limited impact onthe behaviour of outside persons, the financial institutions formulate high standards towards their ownpersonnel. It concerns formal qualifications and professional experience, as well as specific personalitytraits and appropriate behaviour in various situations.These standards are specified in numerous recent ethics codes – documents formulating the socalled‘corporate governance best practices’ in internal and external relations to other people. The aimof this paper is to draw attention to the fact that some of these standards generate in praxis a number ofdilemmas or even conflict situations, when there appears a question of to what extent the application ofa given rule does not breach other rules. Theoretically, corporate governance practices should beinternally consistent. However, everyday experience brings such a multitude of real situations, diversehuman characters or individual reactions that there appears a need for a sensible compromise betweenvalues of equal importance which, in some cases, prove contradicting.